The effects of cGAS-STING inhibition in liver disease, kidney disease, and cellular senescence - Wang, Ling; Zhang, Zhengwei; Zhang, Haichao; Zhou, Minmin; Huang, Cheng; Xia, Wenjiang; Li, Jun; You, Hongmei (Frontiers in Immunology, 2024)
The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling pathway is one of the fundamental mechanisms of the body's defense, which responds to the abnormal presence of double-stranded DNA in the cytoplasm to establish an effective natural immune response. In addition to detecting microbial infections, the cGAS pathway may be triggered by any cytoplasmic DNA, which is absent from the normal cytoplasm, and only conditions such as senescence and mitochondrial stress can lead to its leakage and cause sterile inflammation. A growing body of research has shown that the cGAS-STING pathway is strongly associated with sterile inflammation.In this study, we reviewed the regulatory mechanisms and biological functions of the cGAS-STING pathway through its involvement in aseptic inflammation in liver disease, kidney disease, and cellular senescence.